SUPLEMENTASI FITOBIOTIK PEGAGAN (CENTELLA ASIATICA (L.) URBAN) DALAM PAKAN TERHADAP PERFORMAN AYAM BROILER - Harahap, Dahrul Aman (Universitas Riau Kepulauan, 2013)
The purpose of this research was to study the effect of the floor size level and the use of pegagan in the diet (0; 1; and 2%) on performance of broiler chicken. One hundred and eighty broiler chickens, Lohmann strain, male, were randomly devided into 36 groups, which given feed compatibility with period and the maintenance of broiler chicken and drinking water was given ad libitum. Biologic experiment was conducted for 5 weeks to obtain the performance and one week for adaptation before experiment started.. Data was analyzed by using analysed of variance and fallowed (tested by Duncan’s New Multiple Range Test). Result of study indicated that of three space floor levels and pegagan level were significantly effect on feed consumption, average daily gain. Feed conversion, carcass weight and carcass percentage were no significant difference on broiler chicken. There were no interaction between difference of floor space and pegagan levels on feed consumption, average daily gain, weight and carcass percentage.